A Table that Produces DNA (London Journal of Engineering Research, 2023)
How does DNA originate, how does DNA come into being, and what are the rules? According to the Tong Yilogic of "the Tong YiLun Thought", combined with the DNA composition mode that has been found now, after determining that the mechanism of increasing yang in DNA system is that the increase of deoxyribose number causes the transformation order of four bases, the differentiation of deoxyribose, phosphoric acid and bases constitutes 128 kinds of basic DNA, thus forming the cycle table of DNA production.
Keywords: DNA production Table; DNA Cycle Table; DNA properties; DNA Relationship; DNA Number.